A quality assurance and benchmarking framework in an academic library. - Garner, Imogen; Tang, Karen (2009)
This paper explores the journey Curtin University Library has taken in developing a quality assurance program to direct its continuous improvement processes. It discusses the Library’s approach to planning and performance and how benchmarking has been used to demonstrate good practice and identify targets for future success. Currently the Library’s quality assurance approach is supported by frameworks for planning and performance. These frameworks contain benchmarking activities and measures but the Library is developing a third supporting framework to specifically implement systematic benchmarking in the Library. This Library benchmarking framework reflects the overall objective of benchmarking at Curtin which is to “remain competitive and demonstrate evidence of clearly recognised good practice which will contribute to Curtin’s reputation nationally and internationally”. The Library benchmarking framework identifies important core activities such as collections, facilities, spaces, online services, efficient & effective processes, planning & quality processes, collaborative partnerships, sustainability etc that can contribute to success. It addresses identifying national and international partners with good practices that are willing to work together and share information. These partners may include other libraries, other cultural institutions and service industries. The framework identifies appropriate methodology/ies to be used including measurements of inputs, processes, outputs and outcomes using a range of performance measures. It is expected that the benchmarking framework will significantly contribute to the Library’s objectives to be: • A quality library that is best-practice and client-focussed; • A library that is continually improving its services; • A library that adopts innovative new ideas and technologies; and • A library that is efficient and effective.